2020
DOI: 10.1371/journal.pone.0243969
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS knowledge and attitudes assessment among women of child-bearing age in South Sudan: Findings from a Household Survey

Abstract: This study assessed the determinants that shape HIV knowledge and attitudes among South Sudanese women by analysing a Multiple Indicator Cluster Survey collected from 9,061 women in 9,369 households. Generalised linear mixed model regression was performed. Fifty percent of respondents were aware of HIV/AIDS, with 21% and 22% exhibiting good knowledge and positive attitudes towards people with HIV/AIDS, respectively. When controlled for individual and community-level variables, younger women (AOR = 1.28, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(41 reference statements)
2
7
1
Order By: Relevance
“…Furthermore, a Nigerian study discovered that the prevalence of HIV among female teenagers was 7.4%, compared to 1.8% among older women (34). Contrary to our ndings, a study done in South Sudan showed that being a young woman was protective against low knowledge of HIV (21).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a Nigerian study discovered that the prevalence of HIV among female teenagers was 7.4%, compared to 1.8% among older women (34). Contrary to our ndings, a study done in South Sudan showed that being a young woman was protective against low knowledge of HIV (21).…”
Section: Discussioncontrasting
confidence: 99%
“…This study's prevalence was almost like that seen in a study conducted on Sub-Saharan African women of reproductive age (38.56%) (12). The prevalence of comprehensive knowledge of HIV in other studies done in Uganda (23.1%) (27), Ethiopia (25.2%) (29), South Sudan (21.21%) (21), and Bolivia (31%) (22) was lower than for our study. Contrary to our ndings, a study conducted in Bangladesh (52.2%) (23) and Pakistan (68%) (24) found a higher prevalence of knowledge of HIV/AIDS transmission among women.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Globally, women of reproductive age are at risk of acquiring HIV infection and only 30% of them have comprehensive knowledge about HIV/AIDS [4]. According to different scholars, the prevalence of comprehensive knowledge in Africa, particularly in sub-Saharan Africa is low, which ranges from 19.3% in Ethiopia to 48.9% in Burundi [14,17,18]. Different factors such as education, wealth status, place of residence, sex of household head, region, and media exposure are associated with comprehensive knowledge about HIV/AIDS [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies concluded that good knowledge and a positive attitude are important indicators in the prevention of HIV transmission [ 19 , 20 , 21 ]. One study among women of childbearing age in South Sudan showed that women living in urban areas had better knowledge compared to women living in rural areas [ 22 ]. Several studies have been conducted concerning HIV/AIDS prevention [ 23 , 24 ], while scarce literature addresses socio-economic and demographic factors associated with knowledge and attitudes toward HIV/AIDS in Indonesia.…”
Section: Introductionmentioning
confidence: 99%